Learning optics at basic schools by experimentation - Costa, Manuel F. M. (2008)
The main goal, the work of the physicist is to discover to understand and to explain the physical world. To observe, to see critically, is the first fundamental step in this process. The student must not only to understand this deeply, as they must to be taught to see, to observe. This should be the first concern of a physics/science teacher. We may even argue about the interest of explaining, transmitting the concepts if the student is not able to “see” the problems, the situations and is unable to distinguish/discriminate the processes, the problems involved that need to be solved or explained in order for the situations to be understood. It is definitely of utmost importance to early teach the students to observe but also to raise questions, to perform critical analysis, to build new situations and scenarios.